2023
DOI: 10.7573/dic.2023-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Childhood guttate psoriasis: an updated review

Alexander KC Leung,
Benjamin Barankin,
Joseph M Lam
et al.

Abstract: Background Guttate psoriasis is common and affects 0.5–2% of individuals in the paediatric age group. This review aims to familiarize physicians with the clinical manifestations, evaluation, diagnosis and proper management of guttate psoriasis. Methods A search was conducted in July 2023 in PubMed Clinical Queries using the key term “guttate psoriasis”. The search strategy included all observational studies, clinical trials and reviews published within the past 10 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 220 publications
0
2
0
Order By: Relevance
“…A further type of the disease is the so-called “guttate psoriasis”, which is characterized by small, teardrop-shaped papules that often appear after a streptococcal throat infection. This type of PSO is more common in children and young adults [ 21 ]. Rare forms of the disease are the pustular and the erythrodermic PSO; the first can be characterized by the quick development of pus-filled blisters, while in the case of the other type, the entire skin surface becomes red and inflamed, which itches and burns intensely [ 22 ].…”
Section: Characterization and Pathophysiology Of Psoriasismentioning
confidence: 99%
“…A further type of the disease is the so-called “guttate psoriasis”, which is characterized by small, teardrop-shaped papules that often appear after a streptococcal throat infection. This type of PSO is more common in children and young adults [ 21 ]. Rare forms of the disease are the pustular and the erythrodermic PSO; the first can be characterized by the quick development of pus-filled blisters, while in the case of the other type, the entire skin surface becomes red and inflamed, which itches and burns intensely [ 22 ].…”
Section: Characterization and Pathophysiology Of Psoriasismentioning
confidence: 99%
“…AP1S3 has not been shown to have any association with plaque psoriasis, though findings have shown that loss of function mutations in AP1S3 increases the risk of pustular psoriasis independent of CARD14 and IL36RN, with Mahil et al showing that knock out of the gene causes autophagy in keratinocytes, mediating NF-κB activation [17]. Guttate psoriasis is an outlier among subtypes, caused by a preceding streptococcal infection and often clearing within 3-4 months without treatment, though with the potential to develop into plaque psoriasis [18]. Very little is known about the pathogenesis or potential genetic basis of erythrodermic psoriasis due to its rarity, accounting for only 1-2.25% of psoriatic patients [19].…”
Section: Genetic Comparison Of Psoriasis Subtypesmentioning
confidence: 99%